Auxin biosynthesis by Microbacterium testaceum Y411 associated with orchid aerial roots and their efficacy in micropropagation - Yadav, Archana; Mudoi, Kalpataru Dutta; Kumar, Niraj; Geed, Sachin Rameshrao; Gogoi, Parishmita; Sharma, Rabin K.; Saikia, Ratul (Frontiers in Plant Science, 2022)
Root-associated bacteria strongly affect plant growth and development by synthesizing growth regulators and stress-relieving metabolites. The present study is mainly focused on assessing aerial root-associated bacteria of Rhynchostylis retusa (L.) Blume, an endemic epiphytic orchid is responsible for auxin production and influencing plant growth. A bacterial isolate, Microbacterium testaceum Y411 was found to be the most active producer of indole-3-acetic acid (IAA). The maximum IAA production (170µg/mL) was recorded with the bacterium at optimum process parameters such as pH 7, temperature 30 °C and tryptophan 1000 µg/mL in a culture medium for 48 h. The extracted auxin was purified and analyzed by FT-IR, HPLC, and HR-MS indicating bacterial auxin has a similar mass value to 4-chloroindole-3-acetic acid auxin. Furthermore, the bacterial auxin was tested on in vitro propagation of orchid, Cymbidium aloifolium, and 90% seed germination was recorded in Murashige and Skoog’s medium supplemented with bacterial auxin. The novel results obtained in this study are used for agricultural applications and the Microbacterium testaceum Y411 is a valuable biotechnological resource for a natural auxin.